Essential amino acid transporter Lat4 (Slc43a2) is required for mouse development. (16th January 2015) - Guetg, Adriano; Mariotta, Luca; Bock, Lukas; Herzog, Brigitte; Fingerhut, Ralph; Camargo, Simone M. R.; Verrey, François
<x xml:space="preserve">Abstract</x> Key points Lat4 (Slc43a2) transports branched‐chain amino acids, phenylalanine and methionine, and is expressed in kidney tubule and small intestine epithelial cells. Using a new knockout model as a negative control, it is shown that Lat4 is expressed at the basolateral side of small intestine enterocytes and kidney epithelial cells of the proximal tubule, thick ascending limb and distal convoluted tubule. In the Xenopus oocyte expression system, Lat4 is shown to function as a uniporter with symmetric intracellular and extracellular apparent affinities for phenylalanine. Mice lacking Lat4 display a slight intrauterine growth restriction, postnatal malnutrition and early death, presumably as a result of defective amino acid (re)absorption. These results demonstrate the crucial role that the uniporter Lat4 plays for amino acid transport across cellular barriers and mouse development. Abstract Amino acid (AA) uniporter Lat4 (Slc43a2) mediates facilitated diffusion of branched‐chain AAs, methionine and phenylalanine, although its physiological role and subcellular localization are not known. We report that Slc43a2 knockout mice were born at expected Mendelian frequency but displayed an ∼10% intrauterine growth retardation and low amniotic fluid AAs, suggesting defective transplacental transport. Postnatal growth was strongly reduced, with premature death occurring within 9 days such that further investigations were made within 3 days of birth. Lat4 immunofluorescence showed a strong basolateral signal in the small intestine, kidney proximal tubule and thick ascending limb epithelial cells of wild‐type but not Slc43a2 null littermates and no signal in liver and skeletal muscle. Experiments using Xenopus laevis oocytes demonstrated that Lat4 functioned as a symmetrical low affinity uniporter with a K0.5 of ∼5 mm for both in‐ and efflux. Plasma AA concentration was decreased in Slc43a2 null pups, in particular that of non‐essential AAs alanine, serine, histidine and proline. Together with an increased level of plasma long chain acylcarnitines and a strong alteration of liver gene expression, this indicates malnutrition. Attempts to rescue pups by decreasing the litter size or by nutrients injected i.p. did not succeed. Radioactively labelled leucine but not lysine given per os accumulated in the small intestine of Slc43a2null pups, suggesting the defective transcellular transport of Lat4 substrates. In summary, Lat4 is a symmetrical uniporter for neutral essential AAs localizing at the basolateral side of (re)absorbing epithelia and is necessary for early nutrition and development.